Breast Lesion Excision System in the diagnosis and treatment of intraductal papillomas – A feasibility study. Issue 1 (January 2018) - Niinikoski, Laura; Hukkinen, Katja; Leidenius, Marjut H.K.; Ståhls, Anders; Meretoja, Tuomo J.
Abstract: Objectives: This study aims to evaluate the feasibility of Breast Lesion Excision System (BLES) in the treatment of intraductal papillomas. Material and methods: All patients with a needle biopsy –based suspicion of an intraductal papilloma who consequently underwent a BLES procedure at Helsinki University Hospital between 2011 and 2016 were included in this retrospective study. The purpose of the BLES procedure was either to excise the entire lesion or in few cases to achieve better sampling. Results: In total, 74 patients underwent 80 BLES procedures. Pathological diagnosis after the BLES biopsy confirmed an intraductal papilloma without atypia in 43 lesions, whereas 10 lesions were upgraded to high-risk lesions (HRL) with either atypical ductal hyperplasia or lobular carcinoma in situ. Five cases were upgraded to malignancy, two were invasive ductal carcinomas and three were ductal carcinoma in situ. Additionally, 18 lesions were diagnosed as other benign lesions. Four procedures failed. Complete excision with BLES was achieved in 19 out of 43 intraductal papillomas, 6 out of 10 HRL and two out of five malignant lesions. No major complications occurred. The BLES procedure was adequate in the management of the 71 breast lesions. Conclusion: The BLES procedure is an acceptable method for the management of small benign and high-risk breast lesions such as intraductal papillomas in selected patients. Thus, a great amount of diagnostic surgical biopsies can be avoided.